Maternal Protein Malnutrition: Current and Future Perspectives of Spirulina Supplementation in Neuroprotection - Sinha, Shrstha; Patro, Nisha; Patro, Ishan K. (Frontiers in Neuroscience, 2018)
Malnutrition has been widely recognized as a grave burden restricting the progress of underdeveloped and developing countries. Maternal, neonatal and postnatal nutritional immunity provides an effective approach to decrease the risk of malnutrition associated stress in adulthood. Particularly, maternal nutritional status is a critical contributor for determining the long term health aspects of an offspring. Maternal malnutrition leads to increased risk of life, poor immune system, delayed motor development and cognitive dysfunction in the children. An effective immunomodulatory intervention using nutraceutical could be used to enhance immunity against infections. The immune system in early life possesses enormous dynamic capacity to manage both genetic and environment driven processes and can adapt to rapidly changing environmental exposures. These immunomodulatory stimuli or potent nutraceutical strategy can make use of early life plasticity to target pathways of immune ontogeny, which in turn could increase the immunity against infectious disease arising from malnutrition. This review provides appreciable human and animal data showing enduring effects of protein deprivation on CNS development, oxidative stress and inflammation and associated behavioral and cognitive impairments. Relevant studies on nutritional supplementation and rehabilitation using spirulina as a potent protein source and neuroprotectant against protein malnutrition (PMN) induced deleterious changes have also been discussed. However, there are many futuristic issues that need to be resolved for proper modulation of these therapeutic interventions to prevent malnutrition.